Creating Culturally Responsive Services for Vietnamese-Heritage Survivors of Intimate Partner Violence - Ahrens, Courtney (Journal of family violence, 2022)
Despite a population of over two million Vietnamese people in the United States, very few domestic violence shelters employ Vietnamese-speaking staff or provide culturally responsive services. Research on the needs of Vietnamese intimate partner violence (IPV) survivors is also sparse, and very few studies have asked Vietnamese IPV survivors themselves about their service recommendations. To fill this gap in the literature, the current study conducted qualitative interviews and focus groups with 20 Vietnamese IPV survivors and 13 service providers about IPV services for Vietnamese survivors living in the United States. Analytic Induction was used to identify recommendations for culturally responsive services at the practitioner, intervention, and institutional levels. Participant recommendations were primarily at the intervention and institutional levels. At the institutional level, participants recommended more community outreach and education. At the intervention level, participants recommended more comprehensive and long-term services, more accessible services and locations, and incorporating cultural values and norms into services. At the practitioner level, participants recommended hiring bilingual/bicultural staff and providing culturally responsive and trauma-informed training. Much of the cultural competency literature focuses on practitioner skills and knowledge, but findings from the current study suggest that changes at the intervention and institutional level are just as important. Such changes include the development of non-Western service models, relationship-based methods of community engagement, and long-term services to meet survivors’ needs.